EE 511 Solutions to Problem Set 7 1. (i) SXˆ (f ) = |H(f )|2 SX (f ) where H(f ) = −jsgn(f ). Therefore, SXˆ (f ) = SX (f ). (ii) Suppose h(τ ) is the impulse response of the Hilbert transformer, −h(τ ) = h(−τ ) is the impulse response of the inverse Hilbert transformer. Therefore, we have RXX ˆ (τ ) = RX (τ ) ⋆ h(τ ) and RX Xˆ (τ ) = RXˆ (τ ) ⋆ (−h(τ )) = RX (τ ) ⋆ (−h(τ )) = −RXX ˆ (τ ), where ⋆ denotes convolution. From the above result, we have SXX ˆ (f ) = −SX X ˆ (f ). ˆ t ] = R ˆ (0) and E[Xt X ˆ t ] = R ˆ (0). Therefore, we have E[Xt X ˆ t ] = 0. (iii)E[Xt X XX XX (iv) ˆ t+τ )(Xt − j X ˆ t )] RZ (τ ) = E[(Xt+τ + j X = RX (τ ) − jRX Xˆ (τ ) + jRXX ˆ (τ ) + RX ˆ (τ ) = 2RX (τ ) + 2jRXX ˆ (τ ) Therefore SZ (f ) = = = 2SX (f ) + 2jSXX ˆ (f ) 2SX (f ) + 2jSX (f )[−jsgn(f )] 2SX (f )[1 + sgn(f )] ( 4SX (f ) f > 0 = 0 else 2. See Figure 1. Re[SX I X Q (f )] = 0. Im[S I Q (f)] XX S I(f) X 2 1/2 1/2 −2 −1 0 1 2 −2 −1 f Figure 1: 3. See Figure 2. Re[SX I X Q (f )] = 0. 1 0 1 −1/2 2 f −3 −1 0 S I(f) X Im[S I Q (f)] XX 1 1 1 3 −3 f −1 1 3 f −1 Figure 2: 4. ˆt+τ sin 2πfc (t + τ ))(Nt cos 2πfc t + N ˆt sin 2πfc t)] RN I (τ ) = E[(Nt+τ cos 2πfc (t + τ ) + N = RN (τ ) cos 2πfc (t + τ ) cos 2πfc t + RN Nˆ (τ ) cos 2πfc (t + τ ) sin 2πfc t +RNˆ N (τ ) sin 2πfc (t + τ ) cos 2πfc t + RNˆ (τ ) sin 2πfc (t + τ ) sin 2πfc t Since RNˆ (τ ) = RN (τ ) and RNˆ N (τ ) = −RN Nˆ (τ ), we get RN I (τ ) = RN (τ ) cos 2πfc τ + RNˆ N (τ ) sin 2πfc τ = RN (τ ) cos 2πfc τ + RˆN (τ ) sin 2πfc τ Similarly, we have ˆt+τ cos 2πfc (t + τ ) − Nt+τ sin 2πfc (t + τ ))(N ˆt cos 2πfc t − Nt sin 2πfc t)] RN Q (τ ) = E[(N = RNˆ (τ ) cos 2πfc (t + τ ) cos 2πfc t − RNˆ N (τ ) cos 2πfc (t + τ ) sin 2πfc t −RN Nˆ (τ ) sin 2πfc (t + τ ) cos 2πfc t + RN (τ ) sin 2πfc (t + τ ) sin 2πfc t = RN (τ ) cos 2πfc τ + RNˆ N (τ ) sin 2πfc τ = RN (τ ) cos 2πfc τ + RˆN (τ ) sin 2πfc τ ˆt+τ sin 2πfc (t + τ ))(N ˆt cos 2πfc t − Nt sin 2πfc t)] RN I N Q (τ ) = E[(Nt+τ cos 2πfc (t + τ ) + N = RN Nˆ (τ ) cos 2πfc (t + τ ) cos 2πfc t − RN (τ ) cos 2πfc (t + τ ) sin 2πfc t +RNˆ (τ ) sin 2πfc (t + τ ) cos 2πfc t − RNˆ N (τ ) sin 2πfc (t + τ ) sin 2πfc t = RN (τ ) sin 2πfc τ − RNˆ N (τ ) cos 2πfc τ = RN (τ ) sin 2πfc τ − RˆN (τ ) cos 2πfc τ RN Q N I (τ ) = RN I N Q (−τ ) = −RN (−τ ) sin 2πfc τ − RNˆ N (−τ ) cos 2πfc τ = −RN (τ ) sin 2πfc τ + RNˆ N (τ ) cos 2πfc τ = −RN I N Q (−τ ) 2 5. Nt = Wt cos (2πfc t + Θ) − Wt sin (2πfc t + Θ). RN (τ ) = E[(Wt+τ cos (2πfc (t + τ ) + Θ) − Wt+τ sin (2πfc (t + τ ) + Θ)) (Wt cos (2πfc t + Θ) − Wt sin (2πfc t + Θ))] = RW (τ )E[cos (2πfc (t + τ ) + Θ) cos (2πfc t + Θ)] −RW (τ )E[cos (2πfc (t + τ ) + Θ) sin (2πfc t + Θ)] −RW (τ )E[sin (2πfc (t + τ ) + Θ) cos (2πfc t + Θ)] +RW (τ )E[sin (2πfc (t + τ ) + Θ) sin (2πfc t + Θ)] = RW (τ ) cos 2πfc τ − RW (τ )E[sin (2πfc (2t + τ ) + 2Θ)] = RW (τ ) cos 2πfc τ SN (f ) = 1 [SW (f − fc ) + SW (f + fc )] . 2 S (f) N a/2 −fc −W −fc −fc +W f − W fc c Figure 3: 6. (a) SX Q (f ) = SX I (f ) and SX Q X I (f ) = −SX I X Q (f ). (b) See Figure 6c. (c) See Figure 6c. 7. (a) See Figure 4. (b) See Figure 4. (c) SX Q (f ) = SX I (f ) and SX Q X I (f ) = −SX I X Q (f ). 3 fc + W f S (f) X 1 −14 −11 −9 0 9 11 14 f (MHz) SX˜ (f ) 4 −1 −3 −1 0 0 1 4 f S I(f) X Im[S I Q (f)] XX 1 1 1 3 −3 f −1 1 −1 Figure 4: 4 3 f
© Copyright 2025 ExpyDoc